Temperature distribution and its influence on microstructure of alloy AZ31 during semisolid rheo-rolling process. (1st August 2013) - Zhao, Z Y; Guan, R G; Zhang, Q S; Dai, C G; Lee, C S; Liu, C M
Abstract : In the backward slip zone, the buckling direction of the isothermal lines near the surface of the alloy was toward the exit of the roll gap, the buckling direction of the isothermal lines at the centre was toward the entrance of the roll gap and semisolid metal deformation happened. In the forward slip zone, the buckling direction of the isothermal lines was toward the exit of the gap, the bending degree increased from the neutral flow plane to the exit of the roll gap and solid metal deformation took place. The microstructure of the strip became more refined with the decrease in casting temperature. When the casting temperature was between 670 and 690°C and the rolling speed was 0·167 m s −1, the alloy AZ31 strip with cross-section size of 4×160 mm was prepared. The mechanical properties of the product were higher than that of conventional roll casting.